Syntesis and Characterization of Complexes Anthranilic Acid With Some Metal Ions - Al-Noor, I.H.; Al-Dohan, I. A.; Abd-AI-Magide, I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The research includes attempts to prepare anthranil ic acid (C7H7N02) complexes with some metals: [Pd (II), Fe(ll), and Fe (Ill)) which have been characterized by using: Thermal stability (melti ng point, d composition poit), molar conductivity, IR, UV-visible spectra, elemental analysis (C-H-N) and magnetic properties. The general formula has been given for the prepared complexes:- - M(C2H6N02)2 Where M= [Pd(ll), Fe(TI), Hg(ll)] :.. M(C1H6N02)l Where M= [Fe(llf)]